Investment law No. 72/2017 = قانون الاستثمار رقم 72 لسنة 2017 - Egypt; The middle east library for economic services, translator. (2025)
Part-I: General provisions Chapter - 1: Chapter- 2: Definitions Investment objectives and principles 9. Part- 2: Investment guarantees and incentives Chapter - 1: Chapter - 2: Chapter - 3: Investment guarantees Investment incentives Community responsibility of the investor 91 Part-3: Investment systems Chapter - 1: Chapter - 2: Chapter - 3: Chapter - 4: System of investment in the free zones Chapter - 5: Internal investment system System of investment in the investment zones System of investment in the technological zones 25 28 Provisions of incorporation of companies and establishments and post-incorporation services Allocation of the real estate required for the establishment of the investment projects Chapter - 6: Part-4: Bodies in charge of investment affairs Chapter - 1: Chapter - 2: Supreme council for investment General authority for investment and free zones Part - 5: Investment dispute resolution Chapter - 1: Chapter - 2: Appeal committee Ministerial committee for settlement of investment disputes Ministerial committee for settlement of disputes arising from investment contracts Amicable ways of dispute resolution, arbitration and mediation center 65 Chapter